Solvents and solvent effects in organic chemistry - Reichardt, Christian 1979-; Welton, Thomas (Wiley-VCH, 2011)
Now in its 4th edition, this remains the ultimate reference for all questions regarding the properties and effects of solvents in organic chemistry. Retaining its proven concept, the handbook is completely updated and contains 15% more content, including new chapters on "Solvents and Green Chemistry", "Classification of Solvents by their Environmental Impact", and "Ionic Liquids". From the contents:Solute-Solvent InteractionsClassification of SolventsSolvent Effects on the Position of Homogeneous Chemical Equilibria, on the Rate of Homogeneous Chemical Reactions and on Absorption Spectra of Or